Pelatihan Peningkatan Literasi Keuangan Keluarga Melalui Perencanaan Dana Pendidikan Anak Di Village Gombak Kuala Lumpur Malaysia - Budiandriani Budiandriani; Mahfudnurnajamuddin Mahfudnurnajamuddin; Mapparenta Mapparenta (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Managing family finances is not easy, but it is also not difficult if we know how. Good family financial management is the key to a family's success. Both husband and wife have responsibility for managing family finances, so husband and wife must be able to manage expenses well. For the financial scope in a family, financial management is mostly carried out by a wife as someone who is responsible for managing the household. Having a role as family financial manager, a wife must have knowledge about managing family finances. Starting from recording routine expenses, knowing the family's short, medium and long term needs, to setting aside for future savings. The results achieved through the training provided can increase understanding of family financial planning, participants are also able to make financial plans that are useful in managing household finances. This training is able to increase the training participants' awareness of the importance of family financial planning, then increase the training participants' motivation to create or prepare a budget, save and invest in managing finances. Training participants are able to prepare and simulate financial management in the process of preparing financial planning from the total income they have and the budget allocation that must be made to make it easier for families to manage their finances.